Difficulties of iron-deficiency anemia diagnostics - I. V. Mayev; D. T. Dicheva; D. N. Andreyev; Yu. S. Subbotina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of clinical case presentation. To illustrate difficulties of detection of sources of gastro-intestinal bleeding (GIB) at investigation of patient with severe chronic iron-deficiency anemia.Key points. At the moment of hospital admission in obvious cause of GIB has not been revealed. At complex investigation potential sources of blood loss were found out: hiatal hernia (HH) and diverticula of the large intestine. Pathology data in some cases are complicated both by overt clinical GIB, and microlosses. Presented case illustrates extremely high adaptive potential of female body to chronic blood loss - patient continued to work down to the moment of hospital admission. Definite feature of presented case is the dissociation between severity of anemia and absence of clinical symptoms of HH and diverticular disease.Conclusion. Presented case emphasizes exclusive importance of control of total blood count in women in postmenopausal period and necessity in prophylactic medical examination of patients.